PEMETAAN PENCEMARAN LINDI MENGGUNAKAN METODE GEOLISTRIK 3 DIMENSI - Alaydrus, Alfina Taurida; Minardi, Suhayat; Ardianto, Teguh (IKIP Mataram, 2014)
One of the impacts of waste management is the presence of side-residual landfill waste that causes pollution potential of pollutants results in the form of decaying garbage leachate. This contamination occurs around the landfill Kebon Kongok impacting environmental degradation around the landfill area. To determine the extent to which and how the subsurface conditions around the landfill Kebon Kongok it will do the mapping and modeling using 3-dimensional (3D) geoelectrical method. The study was conducted on 3 pieces of lines are trending relative Southwest-Northeast. Each track has a length of 150m and retrieval of data using a dipole – dipole configuration-with spacing of 10m length. Resistivity measurements carried out with resistivitimeter GL-4100 GSound type and processed with software Res3Dinv. From the analysis it can be concluded that the entire study area has been contaminated by leachate polution, especially in the surface layer to a depth of 13.9 meters.